Interferon regulatory factor 3 mediates effective antiviral responses to human coronavirus 229E and OC43 infection - Duncan, Joseph K. Sampson; Xu, Danyang; Licursi, Maria; Joyce, Michael A.; Saffran, Holly A.; Liu, Kaiwen; Gohda, Jin; Tyrrell, D. Lorne; Kawaguchi, Yasushi; Hirasawa, Kensuke (Frontiers in Immunology, 2023)
Interferon regulatory factors (IRFs) are key elements of antiviral innate responses that regulate the transcription of interferons (IFNs) and IFN-stimulated genes (ISGs). While the sensitivity of human coronaviruses to IFNs has been characterized, antiviral roles of IRFs during human coronavirus infection are not fully understood. Type I or II IFN treatment protected MRC5 cells from human coronavirus 229E infection, but not OC43. Cells infected with 229E or OC43 upregulated ISGs, indicating that antiviral transcription is not suppressed. Antiviral IRFs, IRF1, IRF3 and IRF7, were activated in cells infected with 229E, OC43 or severe acute respiratory syndrome-associated coronavirus 2 (SARS-CoV-2). RNAi knockdown and overexpression of IRFs demonstrated that IRF1 and IRF3 have antiviral properties against OC43, while IRF3 and IRF7 are effective in restricting 229E infection. IRF3 activation effectively promotes transcription of antiviral genes during OC43 or 229E infection. Our study suggests that IRFs may be effective antiviral regulators against human coronavirus infection.